Effects of folic acid on oxidative damage of kidney in lead-exposed rats - Li, Ning; Wen, Liuding; Yu, Zengli; Li, Tiange; Wang, Tianlin; Qiao, Mingwu; Song, Lianjun; Huang, Xianqing (Frontiers in Nutrition, 2022)
Introduction Lead (Pb) has many applications in daily life, but in recent years, various problems caused by lead exposure have aroused people’s concern. Folic acid is widely found in fruits and has received more attention for its antioxidant function. However, the role of folic acid in lead-induced kidney injury in rats is unclear. This study was designed to investigate the effects of folic acid on oxidative stress and endoplasmic reticulum stress in the kidney of rats caused by lead exposure. Methods Forty specific pathogen-free male Rattus norvegicus rats were randomly divided into control, lead, intervention, and folic acid groups. The levels of SOD, GSH-Px, GSH, and MDA were measured by biochemical kits. The protein levels of Nrf2, HO-1, CHOP, and GRP78 were measured by immunofluorescence. Results This study showed that lead exposure increased the blood levels of lead in mice. However, the intervention of folic acid decreased the levels of lead, but the difference was not statistically significant. Lead exposure causes oxidative stress by decreasing kidney SOD, GSH-Px, and GSH levels and increasing MDA levels. However, folic acid alleviated the oxidative damage caused by lead exposure by increasing the levels of GSH-Px and GSH and decreasing the levels of MDA. Immunofluorescence results showed that folic acid intervention downregulated the upregulation of kidney Nrf2, HO-1, GRP78, and CHOP expression caused by lead exposure. Discussion Overall, folic acid alleviates kidney oxidative stress induced by lead exposure by regulating Nrf2 and HO-1, while regulating CHOP and GRP78 to mitigate apoptosis caused by excessive endoplasmic reticulum stress.